Metabolic and hormonal correlates of molting and regeneration of pelage in Alaskan harbor and spotted seals ( Phoca vitulina and Phoca largha) - Ashwell-Erickson, Susan; Fay, Francis H.; Elsner, Robert; Wartzok, Douglas (Canadian Journal of Zoology, 1986)
Cellular, hormonal, and metabolic changes during annual molts and regeneration of the pelage were studied in two harbor and five spotted seals of different ages. Seals were maintained in an appropriate photoperiod and monitored biweekly to monthly by measuring their serum cortisol, thyroxine, and triiodothyronine and their standardized resting metabolic rate. Concurrently, external signs of their molt (shedding of hair) were recorded, and samples of skin were collected from the midback for histological determination of the duration of the regenerative phase of the pelage cycle. Timing of the molts coincided with those of free-ranging seals in the natural environment. The overall duration of the period of shedding and regeneration, from first descent of the hair bulbs on the face and flippers to full emergence of new hair on the back, was estimated as 120–170 days. During the period of descent of the hair bulbs and initial growth of new hair on the back, the resting metabolic rate declined an average of 18.6% below premolt values, generally reaching its minimum when shedding of the old hair and rapid growth of new hair began. Serum Cortisol generally reached a maximum just before or during the main shedding of hair from the torso, then decreased abruptly to its premolt level or lower during the main period of rapid growth of new hair. Although corticosteroids appear to inhibit protein anabolism, they favor fat catabolism and may in this way help to maintain the slow growth of new hair before and during the first part of the molt. Serum concentrations of thyroid hormones declined to minima early in the molt, then increased to maxima toward the end, when growth of new hair was most rapid.